Neutron irradiation effects in Fe and Fe-Cr at 300 °C. (1st June 2016) - Chen, Wei-Ying; Miao, Yinbin; Gan, Jian; Okuniewski, Maria A.; Maloy, Stuart A.; Stubbins, James F.
Abstract: Fe and Fe-Cr (Cr = 10–16 at.%) specimens were neutron-irradiated at 300 °C to 0.01, 0.1 and 1 dpa. The TEM observations indicated that the Cr significantly reduced the mobility of dislocation loops and suppressed vacancy clustering, leading to distinct damage microstructures between Fe and Fe-Cr. Irradiation-induced dislocation loops in Fe were heterogeneously observed in the vicinity of grown-in dislocations, whereas the loop distribution observed in Fe-Cr is much more uniform. Voids were observed in the irradiated Fe samples, but not in irradiated Fe-Cr samples. Increasing Cr content in Fe-Cr results in a higher density, and a smaller size of irradiation-induced dislocation loops. Orowan mechanism was used to correlate the observed microstructure and hardening, which showed that the hardening in Fe-Cr can be attributed to the formation of dislocation loops and α′ precipitates. Graphical abstract: Addition of Cr in Fe suppressed the mobility of mobile 1/2<111> dislocation loops and increased the proportion of immobile <100> dislocation loops, leading to a transition of loop distribution from highly heterogeneous to uniform.